Organization of Assistance and Training of Healthcare Personnel in Medical Facilities Responding to COVID-19 - Yusupalieva, Gulnora Akmalovna; Ismailov, Uktam Safayevich (Asian Pacific Journal of Environment and Cancer, 2020)
In December 2019, a cluster of patients infected with a new beta coronavirus was identified in Wuhan, China. Initially, this virus was given the provisional name “new coronavirus 2019” (2019-nCoV), and later the international Committee on virus taxonomy (ICTV) assigned it the name SARS-CoV-2. The disease it causes is called “coronavirus disease 2019” (COVID-19). In its documents, WHO calls this virus the COVID-19 virus. Coronaviruses (Coronaviridae) are a large family of RNA - containing viruses that can infect humans and certain animals. In humans coronaviruses can cause a range of diseases (from mild forms of acute respiratory infection to severe acute respiratory syndrome). Four coronaviruses (HCoV-229E, -OC43, -NL63, and-HKU1) are currently known to circulate in the population, which are present year-round in the structure of acute respiratory viral infections and usually cause mild to moderate upper respiratory tract damage. Several countries have managed to reduce or stop human-to-human transmission of the COVID-19 virus. Their actions saved lives and gave the rest of the world extra time to prepare for COVID - 19: get emergency response systems ready, build capacity to detect and care for patients, provide hospitals with facilities, supplies and necessary personnel, and develop life-saving medical interventions. Every country must urgently take all necessary measures to slow the further spread of infection and avoid overloading health systems with the large number of critically ill patients with COVID-19.